Surgical site infection prevention bundle for children submitted to cardiac surgery - Giselle Viana de Andrade; Nayana Maria Gomes de Souza; Ana Caroline Felisola Rocha; Silvania Braga Ribeiro; Viviane Martins da Silva; Luis Adriano Freitas Oliveira (SciELO, 2021)
ABSTRACT Objective: To build and validate the content and appearance of a surgical site infection prevention bundle for children submitted to cardiac surgery. Method: Methodological study in two phases: 1) Bundle construction from an integrative literature review from which interventions have been extracted to compose the instrument; 2) Bundle content and appearance validation by 24 judges. Results: The 24 found articles presented 17 interventions for surgical site infection prevention in this population. Out of them, seven intervention proposals have been chosen to compose the bundle and sent for assessment by judges. The final proposal includes all the seven items chosen in the construction phase and has achieved a content validity index over 0.8 in all items referring to content and appearance. Conclusion: The content and appearance of the developed bundle proposes care for the prevention of surgical site infection throughout the perioperative period.